Propagation and Production of Atlantic St. Johnswort - Mack Thetford; Debbie Miller (EDIS, 2004)
Atlantic St. Johnswort is a herbaceous or semi-woody plant with a decumbent growth habit, spreading from the base and forming a low mat (Bell and Taylor 1982). This plant is a candidate for beach projects requiring planting of interdunal areas and secondary dunes as well as for commercial or home landscapes. Flowers occur from June to September, are terminal and axillary, and may be solitary or in small clusters called cymules or dichasia. Each flower is 1 to 2 cm (0.39 to 0.79 in) in diameter with 5 clear yellow petals (Radford et al. 1983). Atlantic St. Johnswort occurs in sandy woods, scrub, and coastal dunes from south Florida to the Carolinas. This document is Fact Sheet ENH 972, from the Environmental Horticulture Department and the Wildlife Ecology and Conservation Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: March 25, 2004.